CONSUMPTION THEORY AND PROBLEMS IN ISLAMIC CONSUMER BEHAVIOR (International Conference on Social and Islamic Studies, 2022)
Consumption is one of the subdivisions of economics that discusses the efforts made by humans in fulfilling their needs. Islam has regulated how a person should obtain goods that they consume and how to consume them. Consumer behavior in consuming goods or services can be an act that violates the rules set by the Shari'a. Ethics in consumption is not just to fulfill needs and desires but also to give attention to the benefits of consumption (maslahah) so that all activities become worship and obtain blessings in this world and the hereafter.